The pedagogical implications of teacher personal philosophies of science in the school science classroom : an interpretive study. - Milne, Catherine E. (Curtin University, 1993)
This thesis addresses the problematic relationship between teacher personal philosophies of science and teacher pedagogy. The research literature on philosophy of science and its impact on science education identifies the persistence and pervasiveness of traditional philosophies of science, such as inductive-empiricism and positivism, that misrepresent the practice of science. Although researchers have expressed concern about the influence of teacher beliefs in inductive-empiricism and positivism on teacher practice in the science classroom, the results of research in this field are inconclusive.This thesis reports an interpretive research study of three high school science teachers. An interpretive framework was developed in order to assist in the identification of teachers personal philosophies of science. The framework comprises philosophical theories of ontology, epistemology, and theory building, and the key assumptions of major philosophers of science.Interpretive analyses were conducted on classroom discourse in order to examine the influence of the three teachers personal philosophies of science on their teaching practice. Data were collected by means of participant-observation, audio-tape recordings, and teacher and student interviews. The validity of the research was optimised by using triangulation methods.The results of the thesis in the form of general assertions, indicate that experienced teachers personal philosophies of science comprise well-established and strongly integrated networks of ontological, epistemological, and theory building beliefs based on the traditional philosophies of science of inductive-empiricism and positivism. The results indicate also that a strong relationship exists between teachers traditional personal philosophies of science and teacher-centred classroom roles and teaching practices, and that this relationship is reinforced by institutional factors such as curriculum policy and teaching resources, and laboratory design and classroom organisation.These results have important implications for the implementation of constructivist-oriented curriculum reforms in school science.